Rent-a-tutor digital platform business model for online and balanced digital entrepreneurship education - Mohd Fuad, Muhammad Hilmi Firdaus; Noor Shamsudin, Muhammad Nur Arif; Mat Nordin, Mohamad Murshyid; Ahmad Dahlan, Abdul Rahman (Research publish, 2020)
: The objective of this paper is to propose a digital platform business model and solution for balanced education called Rent-A-Tutor. In the era of rapid globalization of online learning that was caused by unfortunate circumstances, namely COVID-19, the application is one of the many attempts to help those that are affected by this pandemic. Rent-A-Tutor benefits everyone by providing an opportunity to learn for a small price as well as to generate side-incomes. Tutors may even volunteer to share their knowledge for free to needy students, if they wish to do so. This paper offers a conceptual digital platform business model for Rent-A-Tutor in the form of the Business Model Canvas (BMC), the Value Proposition Design Canvas (VPC), the Environmental Map (EM), and the Strategy Canvas (SC). The design thinking approach has been adapted in this paper to address quality and balanced education, decent work creation, and unemployment challenges in Malaysia through understanding stakeholders’ needs, and then followed by building conceptual business models using modelling tools such as; the BMC, the VPC, the EM and the SC. The approach includes conducting literature review, benchmarking, and interviews for understanding the needs, challenges, and key problems, formulating and ideating initial business model options in solving the problems, and validation of the initial business model by interviewing the various customer segments. To find out the market demand for this product, a Business Model was constructed to find out the market demand. That includes the EM, the BMC, the VPC, and surveys in order to help further understand the struggles that the students as well as the teachers in Malaysia are experiencing during the pandemic. The researchers found out, through surveys, that the demand is there, and some are struggling with current applications that are being used to replace normal classes and some are due to accessibility problems. Some have not even tried using any online learning applications due to its complexities. Rent-A-Tutor works around those problems to provide a comprehensive solution that will satisfy those that will be using it.